The Relevance of industrial Practice Activities to the Competency Field of Industrial Practice in Faculty of Engineering YSU - Moh Adam Jerusalem; Putut Hargiyarto; Mashoedah Mashoedah (JOURNAL OF EDUCATION, 2013)
This study is aimed at finding  out the comparasion between students' activities in industrial practice  and the curriculum of industrial practice.  The study was a survey.  The population  consisted of students  of the Engineering Faculty taking industrial practice  in 2011. A sample of 268 students was used. The results of the study show that all the activities of industrial practice of all study programs have suitable correspondence with the curriculum of industrial practice.  On assistancy side, industry used discussion, supervision, and giving material as the methods of assistancy. The majority of the industries made use of the discussions that went on when students put up questions to supervisors.